Increased Phospholipid Transfer Protein Activity Is Associated With Markers of Enhanced Lipopolysaccharide Clearance in Human During Cardiopulmonary Bypass - Nguyen, Maxime; Gautier, Thomas; Reocreux, Guillaume; Pallot, Gaëtan; Maquart, Guillaume; Bahr, Pierre-Alain; Tavernier, Annabelle; Grober, Jacques; Masson, David; Bouhemad, Belaid; Guinot, Pierre-Grégoire (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Lipopolysaccharide (LPS) is a component of gram-negative bacteria, known for its ability to trigger inflammation. The main pathway of LPS clearance is the reverse lipopolysaccharide pathway (RLT), with phospholipid transfer protein (PLTP) and lipoproteins playing central roles in this process in experimental animal models. To date, the relevance of this pathway has never been studied in humans. Cardiac surgery with cardiopulmonary bypass is known to favour LPS digestive translocation. Our objective was to determine whether pre-operative PLTP activity and triglyceride or cholesterol-rich lipoprotein concentrations were associated to LPS concentrations in patients undergoing cardiac surgery with cardiopulmonary bypass. Methods: A post-hoc analysis was conducted on plasma samples obtained from patients recruited in a randomized controlled trial.Total cholesterol, high density lipoprotein cholesterol (HDLc), low density lipoprotein cholesterol (LDLc), triglyceride and PLTP activity were measured before surgery. LPS concentration was measured by mass spectrometry before surgery, at the end of cardiopulmonary bypass and 24 hours after admission to the intensive care unit. Results: High PLTP activity was associated with lower LPS concentration but not with inflammation nor post-operative complications. HDLc, LDLc and total cholesterol were not associated with LPS concentration but were lower in patients developing post-operative adverse events. HDLc was negatively associated with inflammation biomarkers (CRP, PCT). Triglyceride concentrations were positively correlated with LPS concentration, PCT and were higher in patients with post-operative complications. Conclusion: Our study supports the role of PLTP in LPS elimination and the relevance of RLT in human. PLTP activity, and not cholesterol rich lipoproteins pool size seemed to be the limiting factor for RLT. PLTP activity was not directly related to post-operative inflammation and adverse events, suggesting that LPS clearance is not the main driver of inflammation in our patients. However, HDLc was associated with lower inflammation and was associated with favourable outcomes, suggesting that HDL beneficial anti-inflammatory effects could be, at least in part independent of LPS clearance.